RADIOGRAPHIC APPEARANCE IN HANDS AND FEET OF RHEUMATOID ARTHRITIS PATIENTS AT A TERTIARY CARE HOSPITAL IN PAKISTAN: Radiographic Appearance of Rheumatoid Arthritis - Adnan, Saqib; Aziz, Wajahat; Ahmed, Aliya (Pakistan Armed Forces Medical Journal, 2015)
Objective: The aim of the study was to see the radiographic appearance (erosions and joint space narrowing [JSN]) in hand and foot joints of patients of rheumatoid arthritis (RA)coming to a tertiary care hospital in Islamabad, Pakistan.Study Design:  Cross-sectional descriptive study.Place and Duration of Study: The study was conducted in Department of Rheumatology at Pakistan Institute of Medical Sciences from June, 2013 till December, 2013.Subjects and Methods: Both male and female patients of RA coming to Rheumatology outpatient department were recruited in the study after taking their consent. X-rays of both hands and feet were performed in each of these patients. These X-rays were scored using simple erosion narrowing score.Results: There were total 153 patients in the study, 121 (79.10%) females and 32 (20.90%) males. The mean duration of RA was 6.36 ± 5.47 years. Joint erosions were found in 142 (92.81%) patients. All of these 142 (100%) patients had hand joint erosions. Only 63 (44.36%) patients had foot joint erosions as well. Radiographic changes (combined erosions and JSN) were found in 3712 (39.13%) hand joints and 335 (9.12%) foot joints.Conclusion: Both erosions and JSN were seen predominantly in hand joints of our RA patients, with the foot joints showing much less radiographic changes. Therefore, doing X-Rays of only hands may be sufficient in RA patients for diagnostic and prognostic purposes.